A water sustainability framework for assessing biofuel certification schemes: Does European hybrid governance ensure sustainability of palm oil from Indonesia?. (10th August 2018) - Kemper, Laura; Partzsch, Lena
Highlights: EU biofuel governance combines mandatory requirements with voluntary certification. The mandatory requirements do not adequately address water sustainability. Only certification schemes with NGO members go beyond mandatory requirements. Industry schemes meet minimum requirements but do not push for more sustainability. Normative power is more likely to be exercised if NGOs partake in hybrid governance.